Problems, Solutions, and Hopes: Online Learning During the Pandemic Era at Elementary School - Widyana, Lestari; Bestari, Ertifa; Prastiwi, Prastiwi; Febriyana, Yunita Dewi; Fadila, Anjani (International Journal Labs, 2022)
Background: The COVID-19 pandemic has an impact on many parties, this condition has penetrated the world of education, the central government to the regional level provides policies to dissolve all educational institutions. Aim: This study aims to determine the problems experienced by teachers during Covid-19 pandemic in which teachers must conduct online learning. Method: This research is a descriptive study using online survey method. The data was collected using online questionnaires to 64 respondents of elementary school teachers. Findings: It was found that 98% of the primary school teachers respondents has conducted online learning during Covid-19 pandemic, and 1 teacher did not use online model. More than 9 medias used by elementary school teachers in Bantul district during the pandemic were offered namely WhatsApps, WhatsApp Web, Google Classroom, Google Group, TeamLink, Microsoft Teams, Kaizala Microsoft, Zoom Meeting & Webinar, Youtube, Google Hangouts, and others.